2011
DOI: 10.1074/jbc.m111.226878
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Transient Receptor Potential Vanilloid 5 (TRPV5) Protein N Terminus in Channel Activity, Tetramerization, and Trafficking

Abstract: The epithelial Ca 2؉ channel transient receptor potential vanilloid 5 (TRPV5) constitutes the apical entry site for active Ca 2؉ reabsorption in the kidney. The TRPV5 channel is a member of the TRP family of cation channels, which are composed of four subunits together forming a central pore. Regulation of channel activity is tightly controlled by the intracellular N and C termini. The TRPV5 C terminus regulates channel activity by various mechanisms, but knowledge regarding the role of the N terminus remains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 41 publications
4
17
0
Order By: Relevance
“…We propose that mutational effects are probably results of disruption of the conformation of this region required for the normal protein maturation process. Rescue of TRPV4 G849A/P851A channel function by lowering incubation temperature is fully consistent with this hypothesis, indicating that misfolding is probably the cause for ER retention and loss of function, as previously documented in other misfolding proteins (30,48,49). Given that segment deletions within a broad neighboring region of the C terminus were tolerable, results from the present study are best explained by a working model assuming that the region around residues of Gly 849 and Pro 851 is essential for correct folding of the TRPV4 channel.…”
Section: Discussionsupporting
confidence: 72%
“…We propose that mutational effects are probably results of disruption of the conformation of this region required for the normal protein maturation process. Rescue of TRPV4 G849A/P851A channel function by lowering incubation temperature is fully consistent with this hypothesis, indicating that misfolding is probably the cause for ER retention and loss of function, as previously documented in other misfolding proteins (30,48,49). Given that segment deletions within a broad neighboring region of the C terminus were tolerable, results from the present study are best explained by a working model assuming that the region around residues of Gly 849 and Pro 851 is essential for correct folding of the TRPV4 channel.…”
Section: Discussionsupporting
confidence: 72%
“…The fully functional mM8-myc appears to be largely distributed in vesicles (Fig. 1C), with a pattern similar to that displayed by other TRP channels when they are overexpressed in HEK293 cells (51). In contrast, the ⌬41-57 deletion displays a substantial overlap with an ER marker (Fig.…”
Section: Distal N-terminal Region Encompassing Positions 40 -60 Ismentioning
confidence: 91%
“…Numerous studies indicate that ER export is limited primarily by quality control (47). For example, studies of several splice variants or TRP channel mutants reported their accumulation in the endoplasmic reticulum due to misfolding or compromised tetramerization rather than trafficking regulation mechanisms (22,43,51). In addition, it is possible that truncations that affect the quaternary structure also impair channel assembly and function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, proteins present at the cell surface were biotinylated with 0.5 mg/ml sulfo-NHS-LC-LC-Biotin (Pierce, Rockford, IL, USA) in PBS-CM for 30 min at 4 1C as previously described. 25 Immunoblots were incubated with mouse anti-HA (Cell Signalling Technology, Danvers, MA, USA). Blots were incubated with sheep horseradish peroxidaseconjugated anti-mouse (Jackson ImmunoResearch, West Grove, PA, USA) and then visualized using the enhanced chemiluminescence system.…”
Section: Biotinylation and Immunoblottingmentioning
confidence: 99%